2007
DOI: 10.1109/tsm.2007.901837
|View full text |Cite
|
Sign up to set email alerts
|

Gate CD Control Considering Variation of Gate and STI Structure

Abstract: We developed a fab-wide advanced process control system to control the critical dimension (CD) of gate electrode length in semiconductors. We also developed a model equation that predicts the gate CD by considering the structures of gate electrode and shallow trench isolation. This prediction model was also used to perform a factor analysis of gate CD variation. The effectiveness of the model in controlling feedforward was evaluated by both simulation and experiment. The CD variation of the wafers was improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…the STI thickness beside transistors placed at the edge of array obtains lowered locally and globally. Kurihara et al [12] reported one side effect related to the gate critical dimension (CD) of MOSFET. Using design of experiments, gate CD is modelled as gate right leftthickmathspace.5emnormalCD=29.0+0.95×normalMCD(w,x,y)+0.10×normalPTK(w,x,y)+0.08normalSTP(w,x,y)masks of critical dimension (MCD), polysilicon thickness (PTK), and shallow trench isolation thickness (steP height) (STP) are the variables of masks CD, polysilicon thickness, and STI step height, respectively.…”
Section: Side Effect Of Sti Cmpmentioning
confidence: 99%
“…the STI thickness beside transistors placed at the edge of array obtains lowered locally and globally. Kurihara et al [12] reported one side effect related to the gate critical dimension (CD) of MOSFET. Using design of experiments, gate CD is modelled as gate right leftthickmathspace.5emnormalCD=29.0+0.95×normalMCD(w,x,y)+0.10×normalPTK(w,x,y)+0.08normalSTP(w,x,y)masks of critical dimension (MCD), polysilicon thickness (PTK), and shallow trench isolation thickness (steP height) (STP) are the variables of masks CD, polysilicon thickness, and STI step height, respectively.…”
Section: Side Effect Of Sti Cmpmentioning
confidence: 99%
“…In addition, the interaction among the across-wafer trench depth, the gap-filled oxide deposition, and CMP polish rate distribution requires the optimization of all related processes to minimize the across-wafer step height variation. This is highly critical for improving the gate CD uniformity [4,5] and the gate profile. More details on such correlation are discussed in the next section.…”
Section: Sti Etchmentioning
confidence: 99%
“…One issue is critical dimension (CD) loss or gain, which is a pattern gap between the mask and etching profiles. 1) For example, the CD variation of gate electrodes, which closely affects the channel length of a transistor and thus device performance, has become increasingly important as integrated circuit device dimensions are scaled down to much less than 100 nm. Thus, a better understanding of plasma-surface interactions during etching continues to be important for the nanoscale control of etched profiles and CDs.…”
Section: Introductionmentioning
confidence: 99%